Real-Life Experiences in Using Open Source for Autonomy Applications - Mohsen Malayjerdi; Raivo Sell; Ehsan Malayjerdi; Mustafa İlhan Akbaş; Rahul Razdan (Engineering Proceedings)
The open-source paradigm is well known for its unique potential to crowd-source innovation with spectacular examples of success, such as Linux. The knowledge base of methods to build more successful open-source communities has been growing with concepts such as independent governance, community building, and funding mechanisms. In mobility, an open-source autonomy stack called Autoware was the basis of a significant public transportation research project called ISEAUTO, and a companion project, PolyVerif, focused on building validation and verification technologies. This paper outlines the real-life experiences of two teams using the Autoware framework, providing lessons and recommendations for improving open-source development.